Study on potentials of Light Oil Air Injection (LOAI) in Malaysia Oil Fields - Mohiuddin, Zeeshan (Universiti Teknologi Petronas, 2007)

(untitled)
Air injection has been used as one of the enhanced oil recovery (EOR) techniques especially to extract the heavy oil. In light oil reservoirs, the thermal EOR method is known as light oil air injection (LOAI). The present research work has been carried out to assess the potentials of LOAI in Malaysian light oil reservoirs. The research project begins with the development of reservoir screening criteria by evaluating the worldwide successful LOAI projects and consultation with the industry experts. In principle, the reservoir screening criteria embeds major reservoir properties such as the reservoir temperature, reservoir pressure, oil viscosity, formation depth and reservoir permeability. Based on the developed screening criteria, Dulang El2/13 and Dulang E14 reservoirs were screened out for further study. Selection of these reservoirs was further verified using PRIze screening software. PRIze screening indicated incremental recovery at the cost of high gas production. Black oil simulations were carried out using eight different configurations of injection and production wells to further investigate the potential of LOAI for Dulang El2/13 and El4 reservoirs.